Potential genetic predisposition for anthracycline-associated cardiomyopathy in families with dilated cardiomyopathy. Issue 1 (21st July 2014) - Wasielewski, Marijke; van Spaendonck-Zwarts, Karin Y; Westerink, Nico-Derk L; Jongbloed, Jan D H; Postma, Aleida; Gietema, Jourik A; van Tintelen, J Peter; van den Berg, Maarten P
Abstract : Objective: Anthracyclines are successfully used in cancer treatment, but their use is limited by their cardiotoxic side effects. Several risk factors for anthracycline-associated cardiomyopathy (AACM) are known, yet the occurrence of AACM in the absence of these known risk factors suggests that other factors must play a role. The purpose of this study was to evaluate whether a genetic predisposition for dilated cardiomyopathy (DCM) could be a potential risk factor for AACM. Methods: A hospital-based registry of 162 DCM families and two hospital-based registries of patients with cancer treated with systemic cancer therapy (n>6000) were reviewed focusing on AACM. Selected patients with AACM/DCM families with possible AACM (n=21) were analysed for mutations in cardiomyopathy-associated genes and presymptomatic cardiological evaluation of first-degree relatives was performed. Results: We identified five DCM families with AACM and one patient with AACM with a family member with a possible early sign of mild DCM. Pathogenic MYH7 mutations were identified in two of these six families. The MYH7 c.1633G>A (p.Asp545Asn) and c.2863G>A (p.Asp955Asn) mutations (one double mutant allele) were identified in a DCM family with AACM. The MYH7 c.4125T>A (p.Tyr1375X) mutation was identified in one patient with AACM. Conclusions: This study further extends the hypothesis that a genetic predisposition to DCM could be a potential risk factor for AACM.